Predictive model for the spherical indentation of composite laminates with finite thickness. (1st October 2016) - Wagih, A.; Maimí, P.; Blanco, N.; Trias, D.
Abstract: The elastic response of composite laminates in contact with a stiff indenter is of immense importance in many applications. With the aim to further extend the knowledge on this subject, the contact problem of a stiff spherical indenter with a composite plate was simulated with a 2D axisymmetric model implemented on a commercial software. A parametric study was carried out numerically to study the effect of the different parameters on the force–indentation response. The results show that the indentation response of an orthotropic laminate is material independent and that it strongly depends on the laminate thickness. The lamina thickness has no significant effect on the force–indentation relation. Also, the effect of hole radius can be neglected for the hollow support experiment. Two simple equations were derived by normalizing and fitting FE results to predict the response of an orthotropic laminate of finite thickness in contact with stiff spherical indenter supported on two different boundary conditions (fully and hollow supported). The predictions of the derived equations were compared with experimental results and the available analytical models in the literature. The presented equations show an excellent correlation with the experimental investigations.